Education Minister Howard Cooke speaking at the Annual Prize Giving - Daily News. (1974)
Education Minister Howard Cooke speaking at the Annual Prize Giving.
Level 1 deterioration.
Located on SCF.
Keywords: Cooke, Howard; Photographs